O pré-seminário São José de Faxinal do Soturno: história, memória e patrimônio da Quarta Colônia - Baccin, Vanessa (2022)
The history of the São José Pre-Seminar is intertwined with the history of Faxinal do Soturno, since the construction of this educational complex meant a lot for the consolidation of education in the city. The result of a joint effort, the work began in 1947 and was completed in 1949, after intense work, when Faxinal still belonged to the municipality of Cachoeira do Sul. In the same year, it began to receive students, but the official opening took place in 1950. It's understood today that the building where the Pre-Seminar used to work, and its history are patrimonies of the people of Faxinal and the region, therefore, they need to be valued and preserved. Thus, this study aimed to propose the creation of a “memory space” inside the complex that was once the Pre-Seminary Palotino and now houses the City Council, some municipal secretariats, the Irmão Ademar da Rocha Photographic Museum, the nucleus of the UAB (Open University of Brazil), among others, intending to have an educational and tourist support character. The complex that makes up the Pre-Seminar testifies to the importance of the role of the Catholic Church and religiosity in the process of construction and consolidation of the Fourth Region of Italian Immigration in the center of RS. The methodology used in the research was qualitative in that it used mainly bibliographic, documentary, and oral sources. Based on research and visits to the collections of the Municipality of Faxinal do Soturno and the Historical Archives of the Nossa Senhora Conquistadora Province (Santa Maria) dos Palotinos for the data collection. Also, conducted interviews with former students of the former institution, as well as members of the local community. From the gathering of these data, they were described and analyzed, culminating in texts that make up the last chapter of this study, as well as being fundamental for the proposal of the product, which is the creation of space (room) of memories that will house the history of the São José Pre-Seminar. Therefore, the present dissertation and the product proposal are the results of the professional master's degree and linked to the History and Cultural Heritage research line, created under the Quarta Colônia Geopark Project. From this, the product idealizes a space where the local population can show the importance of the Pre-Seminar, through the timeline, the entire trajectory of this institution as a faxinalense and regional inserted in a faxinalense a heritage and attractive education policy cultural tourist.